DEMOGRAPHY AND ECONOMIC GROWTH: THE EFFECTS OF POPULATION INCREASE AND AGE STRUCTURE ON ECONOMIC GROWTH - Besong, Etchu (Graduate School of International Studies Ajou University, 2015)
Many economists, demographers and other social scientists in recent years have been strict on the fact that population growth prohibits, promotes, or plays no role in the economic development of a country or region. The debates that have resulted from these assertions or claims have created three different schools of thoughts, and each school of thought had produced evidences or cited theories as a solid base for its argument. These schools of thought comprise of the pessimists, optimists, and neutralists who all represent different debates or arguments on the possible positive, negative or neutral effects of population growth. Following these arguments put forward by the various schools, there is one critical factor that had been left unnoticed which is the age composition of the population. Whether population growth is independent, advantageous, or detrimental to economic growth, will very much depend on the age composition of the population and the roles that members of the various groups will play towards economic development. Africa has a large and unexploited human resource in the form of young men and women between the ages of 25 to 45 whose full potential is yet to be realized and exploited because of insufficient education, health, and social welfare with appropriate employment and labor policies. Nigeria which highly represents this rich continent as its most populous nation, and largest economy will be used as a case study. It will further be used in comparison to Germany which is the European Union’s most populous nation and with a fast growing ageing population, to bring out the positive prospects and advantages that Nigeria possesses to enhance its economy. The West African country can capitalize on these advantages if it adopts and carefully and cautiously pursues the above mentioned policies.
학위논문(석사)--아주대학교 Graduate School of International Studies :국제개발협력과,2015. 2